1995
DOI: 10.1002/ijc.2910600408
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immunohistochemistry and RT‐PCR for detection of CD44v‐expression, a new prognostic factor in human breast cancer

Abstract: In different human tumors, splice variants of the surface glycoprotein CD44 (CD44v) are correlated with advanced stages of tumor growth and metastatic potential. In breast cancer and colon cancer, expression of epitopes encoded by exon v6 on primary tumors is an independent prognostic factor for poor patient survival. Two different screening methods for the detection of CD44 variants in tumors have been applied: immunohistochemistry (IHC) and semi-quantitative reverse transcription PCR (RT-PCR). In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 14 publications
4
100
0
Order By: Relevance
“…Several studies have suggested an important biological role for CD44 in tumour progression and metastasis, and the potential for the use of CD44 variant expression as a clinicopathological marker of disease progression in colorectal (Wielenga et al, 1993), breast (Dall et al, 1995), pancreatic (Takada et al, 1994) and gastric cancers . The finding of a relationship between CD44 variant expression and colorectal cancer progression has not been uniform however (see Finke et al, 1995) (Mulder et al, 1995) (92% vs 67%).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested an important biological role for CD44 in tumour progression and metastasis, and the potential for the use of CD44 variant expression as a clinicopathological marker of disease progression in colorectal (Wielenga et al, 1993), breast (Dall et al, 1995), pancreatic (Takada et al, 1994) and gastric cancers . The finding of a relationship between CD44 variant expression and colorectal cancer progression has not been uniform however (see Finke et al, 1995) (Mulder et al, 1995) (92% vs 67%).…”
Section: Discussionmentioning
confidence: 99%
“…However. in recent studies an excellent correlation between the detection of CD44 isoforms by immrunohistochemistrs and reverse transcription PCR was reported (Dall et al 1995 (Tempfer et al 1996a. b).…”
Section: Statisticsmentioning
confidence: 90%
“…breast. cervical and colorectal cancer (Mulder et al 1994: Kainz et al 1995: Kauffmann et al 1995 al (1996) have reported PFSR to be strongly correlated with high CD44 expression. Therefore.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat tissues were ®xed in 4% paraformaldehyde then embedded in para n wax. Five mm sections were immunostained as described (Dall et al, 1995). For immuno¯uorescence studies, adherent cells were grown on eight well chamber slides (Nunc) and suspension cultures were a xed to silane treated slides using a Cytospin centrifuge (Shandon Southern).…”
Section: Immunohistochemistrymentioning
confidence: 99%